Fixed-term contracts in East and West Germany: Low wages, poor prospects? - Frances McGinnity; Antje Mertens (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
Amid lively debate on the consequences of temporary employment, the paper examines the wages and transitions of temporary employees in Germany using socio-economic panel data from the late 1990s. Compared to simple OLS estimates, using a fixed effects model decreases wage differentials between permanent and temporary workers. A two-step instrumental variables estimator leads to insignificant estimates, suggesting that the contract type is an endogenous variable. Moreover, about 1/5 of male temporary employees experience significantly higher 2 and 10 year wage growth than workers on permanent contracts. Using multinomial logistic regression models we find that many temporary workers move into permanent jobs, often with the same employer. For some temporary employment leads to unemployment, particularly those with low human capital. Positioning ourselves between arguments on the positive and negative consequences of temporary employment, we develop the idea of a two-tier labour market for temporary employment in Germany.
urn:nbn:de:kobv:11-10049370
Keywords: J31; J60; J64; 330; mobility; unemployment; Fixed-term contracts; dynamic wages